Mengungkap Faktor-Faktor Pendorong Pergantian Auditor dengan Reputasi Auditor sebagai Variabel Moderasi - Harry Budiantoro; Perdana Wahyu Santosa; Hesty Juni Tambuati Subing (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2026)
This study aims to examine the effect of audit opinion, firm size, management change, and financial distress on auditor switching, with auditor reputation as a moderating variable, using a quantitative approach on 65 observations of companies listed in the Jakarta Islamic Index (JII) during 2019–2023. The findings reveal that audit report lag and firm size have a negative effect on auditor switching, financial distress has a positive effect, while management change shows no significant effect, and auditor reputation does not moderate these relationships. The managerial implications suggest that companies should maintain audit timeliness and operational stability to avoid unnecessary auditor switching, while carefully managing financial conditions as financial distress significantly increases the likelihood of switching, potentially raising costs and damaging investor trust.